Creative Provocations: Speculations on the Future of Creativity, Technology & Learning - Henriksen, Danah; Mishra, Punya (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book explores the complex, yet critical, relationship between technology and creativity, specifically in educational contexts. Creativity is important for success in today's rapidly changing, radically contingent and hyperconnected world. This is even more relevant in the context of teaching and learning-where the psychological, sociological and cultural aspects of human learning confront the challenges of a rapidly changing, technologically saturated world. Written by some of the foremost thinkers and researchers in the area of creativity and/or technology, the chapters in this volume examine the impact of recent and future technologies on creativity, teaching and learning. Individually and collectively, they help us develop an understanding of this nexus of creativity and technology for education. They offer new perspectives on this rapidly evolving future-exploring issues, paradoxes, tensions, and points of interest for creativity and technology. They position these issues in ways that consider implications for thinking, learning, teaching, and education in general.
Preface -- 1. Blueprints for a Creativity Curriculum -- 2. The Intersection of Human and Artificial Creativity -- 3. Conceiving Creativity and Learning in a World of Artificial Intelligence-A Thinking Model -- 4. East Asian Creative Ecologies in Networked Educational Worlds -- 5. Room to Run: Using Technology to Move Creativity into the Classroom -- 6. Creativity, Embodiment and Ensembles through Technological Interactions in Critical-Creative Higher Education -- 7. The Future of the Fine Arts -- 8. Embodied Creativity and Technology: A Complex Relationship -- 9. What Else Can This Be? Creativity as an Iterative Practice -- 10. Creative Pedagogies with Technology: Future Proofing Teaching Training in Music -- 11. Why we should take a second look at the politics of creativity: The dangers of a celebratory mode -- 12. Teaching (for) Experimental Creativity -- 13. How not to kill creativity -- 14. Engaging Uncertainty: Principles and Provocations for Promoting Creative Learning Futures -- 15. Dialogical Provocations: A Creative Trialogue.
Keywords: Art-Study and teaching; Education; Machine learning; Educational psychology; Creativity and Arts Education; Education; Education; Machine Learning; Educational Psychology